The illusion of time: a study of heterotopic interstitial space and interplay of dynamic movement systems as an architectural strategy to investigate new modes of space making in the age of the network - Patel, Suaad (School of Architecture, Planning and Geomatics, 2018)
Within a thriving modern society, nothing is more important than the constant flux of information, communication, transportation and plethora of other activities all moving and intermingling with one another over time and space. This dissertation is a purely hypothetical project which aims to explore the links and relations between spaces; specifically, the connection between the creations of heterotopic interstitial space within the urban fabric due to the interplay of dynamic movement systems in society. Within this particular project, the role of architecture will focus on a building typology (the heterotopia), which encompasses the merging of movement and stasis to inhabit the void created by the dynamic movement systems within our cities. It will aim to challenge intense, fast paced networks of flows, by temporarily obstructing and exaggerating the fluidity of communication, information, transportation and technology. An architectural system which has the ability to deal with the complexities, multi-layered and multi-dimensional systems of information, communication and transport, that current society has to deal with on a daily basis. A gateway to the city, the potential site location sits on the periphery of the Cape Town CBD- a forgotten area in-between an old industrial region and transport route. The chosen site, now completely derelict, used to once function as a manufacturing and repair warehouse for boats many years ago. This dissertation will focus on an architectural design process which deals with the intertwined existence between people and the datascape/system, within a world of pixelated elements and bits merging together to generate the whole. An architectural revolution brought about by technology, this study of heterotopic interstitial space and the interplay of dynamic movement systems as an architectural strategy, aims to investigate new modes of space making in the age of the network. In so doing, resolve issues of dislocation and disconnection, and ultimately accentuate the importance of 'place' as site.